품종 및 가공방법에 따른 콩 특성 및 Isoflavone 변화 - 정현경(Hyun Kyung Jeong); 이대형(Dae Hyoung Lee); 서재순(Jae Soon Seo); 원선이(Seon Yi Won); 강희윤(Heui Yun Kang); 지정현(Jeong-Hyun Chi) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2019)
본 연구에서는 콩 품종별 가공 방법에 따른 품종별 특성 및 isoflavone 변화를 확인하고 가공에 사용 가능한 콩 품종을 위한 기초자료로 활용하고자 수행하였다. 식감과 관련 있는 가공적성 요소인 종피율은 청자3호는 5.76%로 높았으며 녹풍콩의 종피율은 4.42%로 낮았다. 수분흡수율 증가는 대원콩이 수침 후 6시간까지 급격하게 증가하였으며 14시간 후 수분흡수가 포화되었다. 가공방법별 일반성분 변화에서 무처리 대비 증숙, 볶음 처리 시 무게는 큰 변화를 보이지 않았으나 당침 처리의 경우 콩의 설탕 흡수로 인한 무게는 증가하였다. Isoflavone 함량을 측정한 결과 무처리에서 대원 2,223 μg/g, 녹풍 2,191 μg/g, 만풍 2,005 μg/g 순이었다. 가공처리 후 강풍은 당침과 볶음 처리 후에도 isoflavone 함량이 높게 유지되었으며, 녹풍은 genistein이 증숙, 당침, 볶음에서 가공 후에도 손실률이 적었다. 증숙 시간에 따른 isoflavone 함량 변화는 연풍, 강풍, 대원, 청자3호의 isoflavone 함량 변화가 적었다. 당침시간에 따른 isoflavone 함량은 당침 시 daidzein, glycitein, genistein 3종의 isoflavone 모두 감소하였다. This study examined the characteristics and isoflavone changes in different soybean varieties and processing methods. The seed coat, which is the processing element related to the texture of food, was as high as 5.76% in Cheongja3 and as low as 4.42% in Nokpoong. The water absorption increased rapidly up to 6 h after soaking and the saturation of water absorption occurred after 14 h. The changes in the general composition by the processing method showed no significant difference in the weight of the steamed and roasted soybeans. On the other hand, in the case of the sugar-soaked treatment, the weight of soybean increased due to sugar absorption. The isoflavone content of Daewon, Nokpoong, and Manpoong was 2,223 μg/g, 2,191 μg/g, and 2,005 μg/g, respectively. After processing, Kangpoong maintained high in isoflavone contents even after being sugar-soaked and roasted. Nokpoong showed low loss rate even after processing from steaming, sugar-soaking, and roasting. Yeonpoong, Kangpoong, Daewon, and Cheongja3 showed small changes in the isoflavone contents when steaming time increased. The isoflavone content decreased in the order of daidzein, glycitein, and genistein by the increase of sugar-soaking time. KCI Citation Count: 4